The Philosophical Foundations of the Late Schelling The Turn to the Positive. - McGrath, Sean J. (New Perspectives in Ontology Ser., 2021)
This is the first major effort to systematically organise and evaluate Schelling's arguments for a Philosophy of Revelation and to demonstrate their importance for contemporary debates in speculative realism, new realism and post-secularism.